Penguatan Jaringan Komunikasi LDK (Strategi Pemberdayaan Potensi Keberagamaan Warga di Banyumanik) - Hasyim Hasanah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
This paper describes the strengthening of communication network of Community Da'wah Institution (LDK) as a strategy to empower the potential of religious residents in Banyumanik. This potential empowerment is aimed at the emergence of citizens' religious awareness, through the shifting of communication networks that are taking place in Banyumanik. Subjects consisted of four LDKs and one foundation. The method of devotion uses the principle of Participatory Rural Apraisal (PRA) with the Feminist approach. The results of the mentoring activities indicate that there is still a problem of religious awareness among residents in Banyumanik. Indication of religious awareness problem besides value system, indicated by the absence of consistency of behavior. Efforts are made to reduce the problem of religious awareness